Investigating microbial biofilms within washing machines: novel nanosensor technology enables insights into pH gradients of Pseudomonas aeruginosa biofilms - Hollmann, Birte (2021)
Biofilms are communities of microorganisms that attach to various surfaces and are widely associated with infections in animals and plants. This investigation is focussed on a current and growing concern: the distribution and formation of biofilms in washing machines. Many countries wash clothes at reduced temperatures around 30°C to 40°C rather than at higher temperatures above 60°C that would kill many bacteria. Survival of the bacteria is associated with biofouling, malodour and an increased infection risk due to the distribution of human pathogens such as Pseudomonas aeruginosa into the environment. P. aeruginosa is one of the predominant bacteria found in washing machines and is highly resistant to many antibiotics. Little is known about environmental microniches present in biofilms. This work focuses on the pH variation throughout P. aeruginosa biofilms knowing that the pH can influence biofilm formation and could be an important aspect for the prevention of biofilm formation. Novel pH-sensitive optical nanosensors were used that penetrate P. aeruginosa biofilms and emit fluorescence in response to variation in pH. Using time-lapse imaging, pH changes were tracked in real time at a microcolony and single cell level, which will ultimately facilitate monitoring of environmental changes induced as biocides penetrate biofilms. Furthermore, confocal laser scanning microscopy (CLSM) was used to reveal pH variation within single microcolonies where the core of the microcolonies was more acidic than the outside. Furthermore, a set of P. aeruginosa strains was isolated from household washing machines and identification confirmed by matrix-assisted laser desorption/ionization. Whole genome analysis was performed to identify different genomic features relevant to antimicrobial resistance (AMR) and biofilm formation. CLSM revealed an increased propensity of these isolates to form biofilms compared to the laboratory strain PAO1-N. In addition, the washing machine isolates had a decreased susceptibility to benzalkonium chloride, a biocide used in cleaning products as well as an increase in production of pyocyanin, a toxic substance mainly produced by P. aeruginosa. Furthermore, testing of different washing detergent formulations revealed that they possessed a range of abilities to disrupt biofilm formation or kill P. aeruginosa, which will facilitate the development of more effective washing agents to limit the emergence of AMR within biofilms resident in domestic appliances.